Remote Work Flexibility, Work-Life Balance, and Organizational Commitment on Employee Retention - Gede Satya Wicaksana; Gabriel Amadeus Sitompul; Suhardianto; Gde Bayu Surya Parwita (Journal Management & Economics Review (JUMPER), 2026)
The rapid transformation of the modern workplace, driven by digitalization and the widespread adoption of remote work, has significantly reshaped organizational practices and employee expectations. This study aims to examine the influence of remote work flexibility, work-life balance, and organizational commitment on employee retention. A quantitative research approach was employed using a cross-sectional survey design, with data collected from employees working in remote or hybrid work environments. The sample consisted of 150–250 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results indicate that remote work flexibility has a significant positive effect on employee retention, work-life balance, and organizational commitment. Furthermore, both work-life balance and organizational commitment are found to significantly influence employee retention. The mediation analysis reveals that work-life balance and organizational commitment partially mediate the relationship between remote work flexibility and employee retention. These findings suggest that flexible work arrangements not only directly improve retention but also enhance it indirectly by promoting employee well-being and strengthening emotional attachment to the organization. This study contributes to the growing body of literature on remote work and provides practical implications for organizations seeking to improve employee retention through flexible and supportive work policies.